2012
DOI: 10.1186/1472-6823-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Correction of vitamin D deficiency in critically ill patients - VITdAL@ICU study protocol of a double-blind, placebo-controlled randomized clinical trial

Abstract: BackgroundVitamin D deficiency is associated with multiple adverse health outcomes including increased morbidity and mortality in the general population and in critically ill patients. However, no randomized controlled trial has evaluated so far whether treatment with sufficiently large doses of vitamin D can improve clinical outcome of patients in an intensive care setting.Methods/designThe VITdAL@ICU trial is an investigator-initiated, non-commercial, double-blind, placebo-controlled randomized clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…11 Scandinavian diets contain more vitamin D due to higher fatty fish intake and dairy products supplementation with vitamin D. 11 The baseline prevalence of VDI amongst ICU patients is 30-40%. 12 In this study, we found that 84.6% of COVID-19 ICU patients had VDI, vs. 57.1% of floor patients. Strikingly, 100% of ICU patients less than 75 years old had VDI.…”
Section: Discussionmentioning
confidence: 53%
“…11 Scandinavian diets contain more vitamin D due to higher fatty fish intake and dairy products supplementation with vitamin D. 11 The baseline prevalence of VDI amongst ICU patients is 30-40%. 12 In this study, we found that 84.6% of COVID-19 ICU patients had VDI, vs. 57.1% of floor patients. Strikingly, 100% of ICU patients less than 75 years old had VDI.…”
Section: Discussionmentioning
confidence: 53%
“…The primary outcome in this study was hospital LOS with multiple secondary outcomes. 37 The authors of the VITdAL@ICU study found that there was no statistically significant difference in hospital LOS or ICU LOS between intervention group and placebo group. There was no significant difference between the 2 groups for incidence of mortality, causes of death, severity of disease, or mechanical ventilation.…”
Section: Clinical Trialsmentioning
confidence: 96%
“…6,7,18,19,22,24,[36][37][38][39][40] The timing of when 25(OH)D level was checked relative to critical care initiation seemed to have an influence on the prevalence of deficiency. When vitamin D level was assessed within 7-365 days before ICU admission, the incidence of deficiency tended to be lower 6,18-20 compared with checking 25(OH)D levels closer to the time of ICU admission.…”
Section: Prevalence Of Deficiency In Critical Illnessmentioning
confidence: 99%
“…The VITdAL@ICU trial is an investigator-initiated, noncommercial, prospective, randomized, controlled trial comparing high-dose oral cholecalciferol (vitamin D,) versus placebo treatment in a mixed population of 480 critically ill patients with low 25OHD levels (< 20 ng/mL) at the time of admission to the ICU study enrollment. Patients will receive an initial bolus dose of 540,000 IU of vitamin D, and 90,000 IU of vitamin D^ on a monthly basis for 5 months resulting in a total treatment observation period of 6 months (25). My hope is that this study will shed much needed light on the role of vitamin D in improving outcome in our critically ill patients.…”
mentioning
confidence: 98%